Intercultural language learning: the Indonesian for Teachers Initiative (InTI) experience. (4th July 2019) - Curtis, Richard; Robertson, Ann; Mahony, Inez
ABSTRACT: This study explores the impact of a government-funded program which sought to retrain in-service teachers in regional Queensland as Indonesian language teachers through an Australian university-led program with on-campus and in-country components. The study first examines how the Indonesian for Teachers Initiative (InTI) program's diverse social learning approach to intercultural language learning cultivated the development of the teacher participants' Indonesian language skills and intercultural capability. It then identifies how participants incorporated aspects of Indonesian language and culture into their teaching post-program, contributing to the Australian Curriculum's goal of developing students' intercultural capability.